2016
DOI: 10.1186/s12993-016-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of potassium bromate induces neurobehavioral changes, alters cerebral neurotransmitters level and impairs brain tissue of swiss mice

Abstract: BackgroundPotassium bromate (KBrO3) is widely used as a food additive and is a major water disinfection by-product. The present study reports the side effects of KBrO3 administration on the brain functions and behaviour of albino mice.MethodsAnimals were divided into three groups: control, low dose KBrO3 (100 mg/kg/day) and high dose KBrO3 (200 mg/kg/day) groups.ResultsAdministration of KBrO3 led to a significant change in the body weight in the animals of the high dose group in the first, second and the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…It is therefore conceivable that NIS may play an important role in the exclusion of toxic monovalent anions from the central nervous system and that this may have provided an additional driver of NIS protein evolution in the face of differing species-specific environmental anion exposures. While there is currently no hard evidence to support this speculation, several studies have shown that excess iodide, bromine, and bromate can lead to oxidative stress, DNA damage, and apoptosis, especially in the brain [97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore conceivable that NIS may play an important role in the exclusion of toxic monovalent anions from the central nervous system and that this may have provided an additional driver of NIS protein evolution in the face of differing species-specific environmental anion exposures. While there is currently no hard evidence to support this speculation, several studies have shown that excess iodide, bromine, and bromate can lead to oxidative stress, DNA damage, and apoptosis, especially in the brain [97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have documented that KBrO 3 can induce multiple organ toxicity in humans and experimental animals 5,6,7 . Potassium bromated has deleterious effect on CNS of mice 8 . Potassium bromate causes oxidative damage to essential cellular macro molecules, leading to marked nephrotoxicity and cancer in experimental animals 9 .…”
Section: Article Can Be Accessed Online Onmentioning
confidence: 98%
“…Its traces can be cited in multiple packaged and municipality supply water after ozonization during the filtration process [1]. Also, it is used in improving flour quality and dough conditioning in the baking industry as well as in the preparation of beverages, cheese, and fish paste [2][3][4]. Hence, PB in various consumer items poses mild to severe toxicity to critical organs, viz., the kidney, liver, and brain in the living systems [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It perturbs the redox balance in the cells damaging the structural and functional status of the target tissues and macromolecules. Such derogatory effect, if prolonged, can cause many diseases, including cancer, depending on the dose, duration, and concurrent circumstances in the exposed organisms [ 2 , 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%